Managing Science and Technology: The Mozambican Ecosystem - Muhlanga, Marangaze Munhepe; Lima, Solange Rito; Massingue, Venâncio; Ferriera, João Nuno (My University, 2015)
The Current Research Information System (CRIS) emerges as an embracing paradigm for managing the multitude of Science and Technology (S&T) components and players. Instantiating its concepts and directives in the S&T ecosystems of developing countries allows to save years of progress, bringing these countries directly to the European level regarding S&T management. In this context, this article aims at discussing the challenges and strategies for the implementation of technological platforms for managing S&T, taking Mozambique and its NREN as the primary goal. By identifying and understanding the components of the Mozambican S&T ecosystem, we expect to foster science in developing countries and promote international cooperation.
Keywords: CRIS; Open Access; S&T Management; NRENs; Repositories